Ethics in Teaching Profession - Sultana, Mahbuba (ABC Journal of Advanced Research, 2014)
Ethics is the most concerning issues now a day. The society is becoming corrupted and youth generations are doing unethical activities randomly. Family plays an important role to make the children ethical, but teacher has a great role too regarding this issue. A teacher can raise the morality of a student by encouraging the ethical practices. This paper tried to focus on what is ethics and what is the relation of ethics with the teaching profession and finally tried to recommend a code of ethics for teachers.